2014
DOI: 10.1037/a0035323
|View full text |Cite
|
Sign up to set email alerts
|

In the eyes of the beholder: National identification predicts differential reactions to ethnic identity expressions.

Abstract: Two studies examined how perceivers' national identification influences their implicit and explicit attitudes toward White and non-White ethnic groups whose members express their ethnic identity overtly in public or discreetly in private spaces. Results revealed that at a conscious level, White American perceivers' national identification elicited more negative attitudes toward both White and non-White ethnic groups when members embraced their ethnic heritage in public rather than in private. However, at an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Furthermore, imagined contact with different figures may have different consequences on different measures (i.e., intergroup anxiety and prejudice). Moreover, it has been shown previously that people conclude about the outgroups’ identification with their group from knowing about their values and faith (Kaiser & Pratt‐Hyatt, 2009) or knowing where they practice their native language (Yogeeswaran et al, 2014). In accordance with Kaiser and Spalding (2013), we found that it is the public manifestation of identity which elicited negative reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, imagined contact with different figures may have different consequences on different measures (i.e., intergroup anxiety and prejudice). Moreover, it has been shown previously that people conclude about the outgroups’ identification with their group from knowing about their values and faith (Kaiser & Pratt‐Hyatt, 2009) or knowing where they practice their native language (Yogeeswaran et al, 2014). In accordance with Kaiser and Spalding (2013), we found that it is the public manifestation of identity which elicited negative reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was asserted that negative reactions toward the minority are elicited by minority members’ public expressions of identity more than by their private experiences (Kaiser & Spalding, 2013). Thus, for example, the overt ethnic group identity of an outgroup member was manipulated by presenting biographies of outgroup members speaking their native language in public and/or in private (Yogeeswaran, Adelman, Parker, & Dasgupta, 2014). It was found that Whites directed more negative attitudes toward minority members who were more ethnically identified with their group, that is toward those who spoke their language also in public spheres.…”
Section: Prejudice Toward Strongly Identified Outgroup Membersmentioning
confidence: 99%
“…Research by Yogeeswaran and colleagues explored how national identification affects attitudes-both explicit and implicit-toward a White ethnic group (e.g., Polish Americans) and a non-White ethnic group (e.g., Chinese Americans) depending on whether members of a given ethnic group expressed their ethnic identity in a private or public manner. In the study that examined perceivers' unconscious attitudes, findings indicated that White perceivers' national identification predicted more bias against a non-White ethnic group that expressed their ethnic identity via language in public (Yogeeswaran, Adelman, Parker, & Dasgupta, 2014). Conversely, national identification had no effect on White perceivers' implicit attitudes towards a White ethnic group, regardless of whether they were displaying their ethnic identity in public or private.…”
Section: Other Broad Contributionsmentioning
confidence: 94%
“…Several studies now demonstrate that Whites are implicitly perceived to be more American than Blacks, Hispanics, Asian Americans, and even Native Americans (e.g., Devos & Banaji, 2005;Devos & Ma, 2008;Devos et al, 2010;Nosek et al, 2007;Yogeeswaran, Adelman, Parker, & Dasgupta, 2014, 2011Yogeeswaran & Dasgupta, 2010). Using a process dissociation procedure, research reveals that the tendency to perceive Whites as more authentically American than ethnic minorities is driven by an automatic accessibility bias suggesting that associations between ethnicity and American identity come to mind effortlessly and with little awareness (Devos & Heng, 2009).…”
Section: Implicit and Explicit Construals Of Nationalitymentioning
confidence: 94%